2022
DOI: 10.3389/fpsyt.2021.816342
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support Partially Mediates the Impact of Temperament and Character on Postpartum Depression

Abstract: IntroductionTemperament and character of pregnant women, especially harm avoidance (HA) and self-directedness (SD) have been identified as risk factors for postpartum depression, in addition to poor social support. However, the relationship between these personality traits and social support for depressive symptoms after delivery has not been examined.MethodsData were extracted from a prospective cohort survey on pregnant women conducted in Nagoya, Japan that included the Temperament and Character Inventory (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…There is a large body of research demonstrating inverse associations between perceived social support and postpartum depressive symptoms (Gan et al., 2019; Nakamura et al., 2022; O’Neill et al., 2019; Yim et al., 2015). Regression diagnostics indicated that in the present study, there may be a stress‐buffering effect of social support for a very small subset of the population.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of research demonstrating inverse associations between perceived social support and postpartum depressive symptoms (Gan et al., 2019; Nakamura et al., 2022; O’Neill et al., 2019; Yim et al., 2015). Regression diagnostics indicated that in the present study, there may be a stress‐buffering effect of social support for a very small subset of the population.…”
Section: Discussionmentioning
confidence: 99%